2002
DOI: 10.1128/jvi.76.9.4536-4546.2002
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Vectors Encoding Cholera Toxin or the Heat-Labile Enterotoxin fromEscherichia coliAre Strong Adjuvants for DNA Vaccines

Abstract: DNA vaccines are widely recognized for their ability to elicit cellular as well as humoral immune responses to microbial antigens (23). An important characteristic of DNA vaccines is that they can mimic characteristics of live vaccines due to their ability to induce the de novo production of microbial antigens in both transiently transfected nonimmune cells and antigenpresenting cells in the vaccine inoculation site and nearby draining lymph nodes (12,14,25). The promise of intramuscularly injected DNA vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 51 publications
(74 reference statements)
5
72
2
Order By: Relevance
“…The adjuvants did not improve the antibody responses elicited to the RVFV +NSm vaccine, which was not entirely unexpected. In earlier studies, influences of both sets of vectors on antibody responses were antigen dependent and ranged from no effect to sharp reductions in the immunoglobulin G1 (IgG1)-to-IgG2a ratios [28]. Here, we did not assess the antibody isotypes in the sera of vaccinated mice, thus we do not know if the adjuvants shifted the responses from the normal Th2-type response that we observe after gene gun vaccination of mice toward a more Th1-type response.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The adjuvants did not improve the antibody responses elicited to the RVFV +NSm vaccine, which was not entirely unexpected. In earlier studies, influences of both sets of vectors on antibody responses were antigen dependent and ranged from no effect to sharp reductions in the immunoglobulin G1 (IgG1)-to-IgG2a ratios [28]. Here, we did not assess the antibody isotypes in the sera of vaccinated mice, thus we do not know if the adjuvants shifted the responses from the normal Th2-type response that we observe after gene gun vaccination of mice toward a more Th1-type response.…”
Section: Discussionmentioning
confidence: 73%
“…Co-administration of these genetic adjuvants has been shown to augment the Th1 cytokine responses (gamma interferon) in mice to multiple viral antigens when co-delivered with DNA vaccines. In addition, both adjuvants also increased antibody responses and Th2 cytokine responses (interleukin 4) to certain antigens tested [28].…”
Section: Immunogenicity Of Individual and Combination Dna Vaccines Fomentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, this review shows that DNA vaccines administered by PMED, even in the absence of heterologous boosting or adjuvants, have translated well from the mouse and bench to preclinical large animal species, including nonhuman primates and pigs, and to human clinical trials. New improvements in the PMED technology [72], vector design [25,76,77], including co-formulation of PMED DNA vaccines with adjuvants [78], are in progress to further enhance the potency of particle-mediated DNA vaccines. These eVorts are expected to accelerate the commercialization of PMED as an eVective approach for vaccination against infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has found that plasmids expressing Cholera Toxin (CT) and E. coli Heat Labile Toxin (LT) can greatly enhance cellular immune responses of standard DNA vaccines delivered by PMED. 13,14 To explore if these adjuvants, termed DNA Encoded Immunostimulators (DEIs), also enhanced SGV immunogenicity, experiments were performed to examine the activity of SGV/DEI formulations. These formulas were very potent and may be useful for the development of a vaccine requiring strong cellular responses in humans.…”
Section: Introductionmentioning
confidence: 99%